2014
DOI: 10.3390/ijms15057250
|View full text |Cite
|
Sign up to set email alerts
|

Indian Hedgehog in Synovial Fluid Is a Novel Marker for Early Cartilage Lesions in Human Knee Joint

Abstract: To determine whether there is a correlation between the concentration of Indian hedgehog (Ihh) in synovial fluid (SF) and the severity of cartilage damage in the human knee joints, the knee cartilages from patients were classified using the Outer-bridge scoring system and graded using the Modified Mankin score. Expression of Ihh in cartilage and SF samples were analyzed with immunohistochemistry (IHC), western blot, and enzyme-linked immunosorbent assay (ELISA). Furthermore, we detected and compared Ihh protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…The rise in expression of Col1a1 may indicate that the chondrocytes are reverting to a more fibroblastic phenotype indicative of their attempt to initiate repairs, albeit with the incorrect collagen. This correlates with other work, where more damaging impacts resulted in elevated Col1a1 expression [ 15 ], and with theories of dedifferentiated chondrocytes in OA progression [ 11 , 27 30 ]. The overexpression of Col1a1 has been correlated with chondrocyte hypertrophy in OA [ 31 ] and even focal chondrocyte cluster formation [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…The rise in expression of Col1a1 may indicate that the chondrocytes are reverting to a more fibroblastic phenotype indicative of their attempt to initiate repairs, albeit with the incorrect collagen. This correlates with other work, where more damaging impacts resulted in elevated Col1a1 expression [ 15 ], and with theories of dedifferentiated chondrocytes in OA progression [ 11 , 27 30 ]. The overexpression of Col1a1 has been correlated with chondrocyte hypertrophy in OA [ 31 ] and even focal chondrocyte cluster formation [ 32 ].…”
Section: Discussionsupporting
confidence: 89%
“…HIF-1α also regulates the configuration and maintenance of articular cartilage via the induction of anabolic factors and the suppression of key catabolic factors (36). The migration and invasion of fibroblast-like synoviocytes (FLSs) have also been demonstrated to be critical for the pathogenesis of OA (37,38). Li et al (15) showed that HIF-1α levels contribute to the migration and invasion of FLSs by upregulating the expression of MMP2 and MMP9 via the activation of the NF-κB/HIF-1α signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies using knockout mice have demonstrated that the activation of Hh signal results in a decrease in articular cartilage thickness and proteoglycan content while Ihh signaling inhibition attenuates the severity of OA (11,14). Furthermore, some studies have reported that Ihh was increased in human OA cartilage and synovial fluid and that the elevation of Ihh was associated with the severity of OA cartilage damage (13,15). These results demonstrate that Ihh signaling is critical in cartilage degeneration and OA development of the knee joint.…”
Section: Introductionmentioning
confidence: 89%